ANALISIS TINGKAT PERTUMBUHAN EKONOMI DAN POTENSI EKONOMI TERHADAP PRODUK DOMESTIK REGIONAL BRUTO (PDRB) KABUPATEN PATI TAHUN 2000-2005 - Prishardoyo, Bambang (JEJAK: Jurnal Ekonomi dan Kebijakan, 2008)
Developing the economy in a region is a process in which a regional government and its societymanage and exploit their resources by having a partnership between the regional government andprivate businessmen, so that it stimulate the economy activities or increase the economy growth andthere will be a new wide range of work fields. The problems of the present study are stated as follow:(1)what sectors are the basis for Kabupaten Pati from 2000 to 2005? (2)what are the roles of kabupatenPati and the others areas in supporting the economy growth. The aims of the study are: (1) for knowingwhich economy sectors that become the basis for kabupaten Pati, (2) the roles of Kabupaten Pati andthe others area in supporting the economy growth. This study uses quantitative qualitative approach andthe data analyzed are taken from Kabupaten Pati. Furthermore, in analyzing the data, economy basedmodel which uses location quotient(LQ) analysis, shift share analysis, gravity analysis was chosen.Finally, the LQ analysis showed that the basis sectors that could be developed were agricultural sector(average: 1,66); electricity, gas and water sector (average: 1,27); construction sector (average: 1,14);finance, rent and company services sector (average: 1,71) and the gravity analysis showed that theinteraction between Kabupaten Pati and Kudus was the best and the strongest.Keywords: economic growth, economic base.